Pelaksanaan Pendidikan Kesehatan terhadap Perilaku Hidup Bersih dan Sehat (PHBS) - Trisasri, Ruri; Putri Isriyatil Jannah; Nabela Putri Yanuari (STIKes Surya Global Yogyakarta, 2024)
Background of Study: Boarding School are Islamic education dormitories that need attention about health because many students live in them. Boarding schools are strategic place to increase students’ knowledge about health to change attitudes and behavior of individual hygiene. This can be implemented by providing health education for students by instilling clean and healthy living behavior to improve healthy living skills from an early age. The aim of this study was to correlate clean and healthy living behavior of high school students in Ibnul Qoyyim Boarding School for Boys. Methods: Research design used in this study was cross sectional. Population in this research was all high school students in Ibnul Qoyyim Boarding School for boys. The sampling technique used was purposive sampling technique, so the samples taken were 86 students with inclusion criteria. Data analysis used SPSS application with Chi-square test (p < 0,05) to correlate health education with clean and healthy living behavior by 8 indicators from Ministry of Health Indonesia. Results: The most respondent were 16 years old (30.2%). And 72% have received Health Education but only 12,8% have applied clean and healthy living behavior. The result of statistical test showed that there was no correlation in correlation between health education with clean and healthy living behavior (p value = 0.681; PR = 1.180). But, from Prevalence Ratio value, the implementation of health education is a factor that can affect PHBS in students by 1,180 times compared to students who have not received health education for the last 6 months. Conclusion: There was no correlation between health education with clean and healthy living behavior of high school students in Ibnul Qoyyim Boarding School for Boys. Keywords: Health Education, Health Behavior, Boarding School